2010
DOI: 10.1186/1748-717x-5-40
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of coplanar and noncoplanar intensity-modulated radiation therapy and helical tomotherapy for hepatocellular carcinoma

Abstract: BackgroundTo compare the differences in dose-volume data among coplanar intensity modulated radiotherapy (IMRT), noncoplanar IMRT, and helical tomotherapy (HT) among patients with hepatocellular carcinoma (HCC) and portal vein thrombosis (PVT).MethodsNine patients with unresectable HCC and PVT underwent step and shoot coplanar IMRT with intent to deliver 46 - 54 Gy to the tumor and portal vein. The volume of liver received 30Gy was set to keep less than 30% of whole normal liver (V30 < 30%). The mean dose to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 44 publications
1
35
1
Order By: Relevance
“…Several modalities, including surgical resection, transcatheter arterial chemoembolization (TACE) and arterial infusion chemotherapy, percutaneous ethanol injection therapy, microwave coagulation therapy, radiotherapy and liver transplantation, have been used in the treatment of HCC (2,3). The optimal choice for patients with early HCC is surgery, as resection may be easily performed, with low mortality rates (4).…”
Section: Introductionmentioning
confidence: 99%
“…Several modalities, including surgical resection, transcatheter arterial chemoembolization (TACE) and arterial infusion chemotherapy, percutaneous ethanol injection therapy, microwave coagulation therapy, radiotherapy and liver transplantation, have been used in the treatment of HCC (2,3). The optimal choice for patients with early HCC is surgery, as resection may be easily performed, with low mortality rates (4).…”
Section: Introductionmentioning
confidence: 99%
“…This goal can be achieved by implementing techniques such as 3D‐conformal radiation therapy, intensity‐modulated radiation therapy (IMRT), and intensity‐modulated arc therapy (IMAT). In combination with these techniques, noncoplanar beams play an important role, especially when the organs at risk need to be better spared without sacrificing the dose distribution conformity of the tumor 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 . For example, Wang et al (9) showed that in 80% of the cases noncoplanar beam configurations were more effective than the coplanar beams to spare the anatomic structures critical to vision for the treatment of paranasal sinus carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The use of three-dimensional static conformal radiotherapy (3D-CRT) for PVTT was also reported; the local control rate ranged from 37.5–57.9%, and the median survival period ranged from 6.7–10.7 months [1420]. In addition, intensity-modulated radiotherapy (IMRT), volumetric-modulated arc therapy (VMAT), and tomotherapy were also employed for treating PVTT [21, 22]. However, to the best of our knowledge, dose-escalation studies using VMAT for PVTT have not been reported.…”
Section: Introductionmentioning
confidence: 99%